2017
DOI: 10.1038/ng.3978
|View full text |Cite
|
Sign up to set email alerts
|

Exome chip meta-analysis identifies novel loci and East Asian–specific coding variants that contribute to lipid levels and coronary artery disease

Abstract: Most genome-wide association studies have been conducted in European individuals, even though most genetic variation in humans is seen only in non-European samples. To search for novel loci associated with blood lipid levels and clarify the mechanism of action at previously identified lipid loci, we examined protein-coding genetic variants in 47,532 East Asian individuals using an exome array. We identified 255 variants at 41 loci reaching chip-wide significance, including 3 novel loci and 14 East Asian-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(119 citation statements)
references
References 40 publications
5
107
2
1
Order By: Relevance
“…Several studies have demonstrated the association between ChREBP gene polymorphisms and plasma TG levels or glucose‐related traits . Recently, a functional coding variant in ChREBP (rs35332062) was identified in both East Asian and European populations with similar MAF (0.117 in East Asian and 0.109 in European populations, respectively) . However, only the rs1051943 A allele was found in our study population, which was different from the European population (rs1051943 MAF = 0.07).…”
Section: Discussioncontrasting
confidence: 71%
“…Several studies have demonstrated the association between ChREBP gene polymorphisms and plasma TG levels or glucose‐related traits . Recently, a functional coding variant in ChREBP (rs35332062) was identified in both East Asian and European populations with similar MAF (0.117 in East Asian and 0.109 in European populations, respectively) . However, only the rs1051943 A allele was found in our study population, which was different from the European population (rs1051943 MAF = 0.07).…”
Section: Discussioncontrasting
confidence: 71%
“…We performed association analysis between autosomal genetic variants and 38 biomarkers in 318,984 unrelated selfidentifiedWhiteBritish individuals of European ancestry and stratified the association into three bins: 1) proteintruncating (27,816), 2) proteinaltering (87,407), and 3) noncoding (MAF > 1%, 1000 Genomes Phase 1 variants also present in Haplotype Reference Consortium [HRC], 9,444,561 17 ) ( Figure 2A ). Comparison of effect sizes estimated across 42 comparison studies with 25 of the biomarkers show overall high agreement (correlation greater than 0.5 for 33 comparisons, Supplementary Figure 5 , Supplementary Table 4 for comparison) across previous studies of lipids 1,2,18,19 , glycaemic 20 , 21 , kidney function 22,23 , liver function 20 , and other biomarkers measurements 24,25 .…”
Section: Genetics Of Biomarkerssupporting
confidence: 54%
“…Notably, most of the dyslipidemia genes are also linked to GWAS signals, indicating that common variants at these loci also contribute to lipid levels [56,57,58,38,59]. For example, 7 out of 10 genes associated with monogenic disorders of LDL-cholesterol levels are within the set of 57 genome-wide significant hit regions from a GWAS of LDL levels [20,57].…”
Section: Discussionmentioning
confidence: 99%